STRATEGI PEMBERDAYAAN EKONOMI SYARIAH DI PESISIR DELI SERDANG: MENGATASI KENDALA AKSES MODAL USAHA PELAKU USAHA UMKM UNTUK PENGEMBANGAN BISNIS - Rasikhah Zahwah Syafitri; Darmawan Darmawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Economic growth in Deli Serdang Regency, which has experienced many fluctuations over the last five years, presents challenges that require strategic intervention. In this context, micro, small and medium enterprises (MSMEs) are emerging as a key sector ready to address these challenges and drive economic development. This research aims to examine and analyze the role of MSMEs in encouraging economic growth in Deli Serdang Regency. Using qualitative descriptive data analysis, this research highlights the motivation and contribution of MSMEs to the local economy. The results show that the contribution of MSMEs of 49.25% to Deli Serdang's economic growth is quite large. These results are valuable references and insights, providing important information for future research efforts and policy formulation to support and enhance economic development in the region